Learning how to use a digital workbench: guided or explorative? - Buchner, Josef; Vonarx, Anne; Pfänder, Peter; Michael Kerres (Orchestration of Learning Environments in the Digital World, 2022)
In this study, vocational education teachers and research assistants learned how to use a new digital workbench through a guided or an unguided instructional approach. We investigated the influence of the two instructional approaches on different learning objectives. Results show that guided instruction led to significantly better performance on a structured learning objective (quantity of tasks fulfilled), better performance on a second structured learning objective (quality of the fulfilled tasks), and similar results to a more unstructured learning objective (explore the functionalities of the workbench). Furthermore, we found that participants in the guided condition reported less temporal stress and higher self-confidence to perform well on the given tasks. With regard to the attitudes toward the use of the workbench, the participants in the unguided group showed slightly more positive values, although the differences were not statistically significant. In conclusion, we found advantages for the guided instructional approach with worked-out examples when participants have to learn how to use a totally new digital workbench.